THE IMPLEMENTATION OF HOTEL TAX COLLECTION POLICY BASED ON REGIONAL REGULATION NUMBER 18 OF 2011 IN SUKABUMI REGENCY - RIKY YULANDA; IKE RACHMAWATI; ERRY SUNARYA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This research is motivated by the problem that local tax revenue is still not optimal from the hotel tax sector in Sukabumi Regency. The hotel tax collection policy in Sukabumi Regency is based on Regional Regulation number 18 of 2011, but in its implementation there are still obstacles so that the implementation of the policy is hampered. This study aims to determine (1) the implementation of local tax collection policies based on Regional Regulation number 18 of 2011 concerning hotel taxes in Sukabumi Regency; (2) knowing the obstacles faced in the implementation of hotel tax collection policies in Sukabumi Regency; (3) knowing the efforts made in overcoming the obstacles faced in the implementation of the Hotel Tax collection policy by the Regional Government of Sukabumi Regency. In order to approach this problem, Edward III's theoretical reference is used. This research is a qualitative descriptive study. The data used are primary data obtained from direct interviews with policy implementers and taxpayers. Data collection techniques using interview techniques, observation and documentation. Then the analysis and interpretation of the selected data is carried out, to then draw a conclusion. Furthermore, the writing and construction of research results are carried out. The results of the study conclude that in general the implementation of hotel tax collection policies in Sukabumi Regency has been going well, it's just that there are several dimensions that need to be improved, such as the dimensions of resources that require additional budgets in order to optimize local tax collection in Sukabumi Regency and dimensions of the bureaucratic structure that require improvements. further, both in terms of the preparation of Standard Operating Procedures (SOP) as well as in its implementation in the field.